Women awaken faster than men after electroencephalogram-monitored propofol sedation for colonoscopy: A prospective observational study. Issue 10 (October 2017) - Riphaus, Andrea; Slottje, Mark; Bulla, Jan; Keil, Carolin; Mentzel, Christian; Limbach, Vera; Schultz, Barbara; Unzicker, Christian
Abstract : BACKGROUND: Sedation for colonoscopy using intravenous propofol has become standard in many Western countries. OBJECTIVE: Gender-specific differences have been shown for general anaesthesia in dentistry, but no such data existed for gastrointestinal endoscopy. DESIGN: A prospective observational study. SETTING: An academic teaching hospital of Hannover Medical School. PATIENTS: A total of 219 patients (108 women and 111 men) scheduled for colonoscopy. INTERVENTION: Propofol sedation using electroencephalogram monitoring during a constant level of sedation depth (D0 to D2) performed by trained nurses or physicians after a body-weight-adjusted loading dose. MAIN OUTCOME MEASURES: The primary end-point was the presence of gender-specific differences in awakening time (time from end of sedation to eye-opening and complete orientation); secondary outcome parameters analysed were total dose of propofol, sedation-associated complications (bradycardia, hypotension, hypoxaemia and apnoea), patient cooperation and patient satisfaction. Multivariate analysis was performed to correct confounding factors such as age and BMI. RESULTS: Women awakened significantly faster than men, with a time to eye-opening of 7.3 ± 3.7 versus 8.4 ± 3.4 min ( P  = 0.005) and time until complete orientation of 9.1 ± 3.9 versus 10.4 ± 13.7 min ( P  = 0.008). The propofol dosage was not significantly different, with some trend towards more propofol per kg body weight in women (3.98 ± 1.81 mg versus 3.72 ± 1.75 mg, P  = 0.232). CONCLUSION: The effect of gender aspects should be considered when propofol is used as sedation for gastrointestinal endoscopy. That includes adequate dosing for women as well as caution regarding potential overdosing of male patients. TRIAL REGISTRATION: ClinicalTrials.gov (Identifier: NCT02687568).